Fear & memory in the Brazilian army and society, 1889-1954 - Smallman, Shawn C. (University of North Carolina Press, 2002)
For more than half a century, the Brazilian army used fear and censorship to alter history and create its own political myths. Drawing on oral histories, secret police documents and other sources recently made available, the author offers a revisionist interpretation of Brazil's political history.